The sourcebook for teaching science, grades 6-12 : strategies, activities, and instructional resources - Herr, Norman (San Francisco : Jossey-Bass, 2008)
Contains resources for teaching science in grades six to twelve, featuring ideas, activities, lesson plans, and strategies that cover physics, chemistry, biology, and the Earth and space sciences.
Includes bibliographical references (p. 567-575) and index.
Professional.
Professional
Keywords: Science -- Study and teaching (Middle school); Science -- Study and teaching (Secondary); Science -- Study and teaching